Sensitivity improvement in fluorescence‐based particle detection. Issue 9 (17th June 2014) - Kettlitz, Siegfried W.; Moosmann, Carola; Valouch, Sebastian; Lemmer, Uli; Zucker, Robert M.
Abstract Microfluidic flow cytometers are highly interesting candidates for biomedical point‐of‐care applications. However, the sensitivity, reliability, and throughput of these systems must be improved to provide the full functionality of established flow cytometric systems. One proposed method to improve fluorescence detection systems is to use spatial modulation techniques. We derive the noise‐related statistics and calculate the coefficient of variation for a detection system with and without spatial modulation. We measure the noise properties of a nonmodulated microfluidic fluorescence particle detection system and analyze the possible performance gains using spatial modulation. © 2014 International Society for Advancement of Cytometry